Metal mining in the southern Andes - Silva Preciado, Alfredo (1985)
Mining in Peru dates back to pre-Inca times, where the Peruvian aborigine incorporated mining resources into their struggle for survival and domination of a hostile environment. In the Inca era, a large number of mines were exploited in the southern Andes. According to the Peruvian historian Luis E. Valcárcel, in his "History of Ancient Peru", the greatest wealth of gold, silver, tin, copper and other metals were extracted in the area from Cusco to Tarija. The main mines that we can mention are: Potosí, Chichas, Lipes, Charcas, Oruro, Carangas, Bereguela, Sicasica, Pocajes, Tiahuanaco, Lorecaja, San Antonio de Esquilache, Lampa, Pomasi, Santa Lucía, Carabaya.